Interpreting the Spitzer/IRAC colours of 7 ≤ z ≤ 9 galaxies: distinguishing between line emission and starlight using ALMA. Issue 3 (16th July 2020) - Roberts-Borsani, G W; Ellis, R S; Laporte, N
ABSTRACT: Prior to the launch of JWST, Spitzer /IRAC photometry offers the only means of studying the rest-frame optical properties of z >7 galaxies. Many such high-redshift galaxies display a red [3.6]−[4.5] micron colour, often referred to as the 'IRAC excess', which has conventionally been interpreted as arising from intense [O iii ]+H β emission within the [4.5] micron bandpass. An appealing aspect of this interpretation is similarly intense line emission seen in star-forming galaxies at lower redshift as well as the redshift-dependent behaviour of the IRAC colours beyond z  ∼ 7 modelled as the various nebular lines move through the two bandpasses. In this paper, we demonstrate that, given the photometric uncertainties, established stellar populations with Balmer (4000 Å rest frame) breaks, such as those inferred at z > 9 where line emission does not contaminate the IRAC bands, can equally well explain the redshift-dependent behaviour of the IRAC colours in 7 ≲ z  ≲ 9 galaxies. We discuss possible ways of distinguishing between the two hypotheses using ALMA measures of [O iii ] λ88 micron and dust continuum fluxes. Prior to further studies with JWST, we show that the distinction is important in determining the assembly history of galaxies in the first 500 Myr.